Reduced Lateral Root Branching Density Improves Drought Tolerance in Maize - Zhan, Ai; Schneider, Hannah; Lynch, Jonathan P. (Plant physiology (Bethesda), 2015)
An emerging paradigm is that root traits that reduce the metabolic costs of soil exploration improve the acquisition of limiting soil resources. Here, we test the hypothesis that reduced lateral root branching density will improve drought tolerance in maize (Zea mays) by reducing the metabolic costs of soil exploration, permitting greater axial root elongation, greater rooting depth, and thereby greater water acquisition from drying soil. Maize recombinant inbred lines with contrasting lateral root number and length (few but long [FL] and many but short [MS]) were grown under water stress in greenhouse mesocosms, in field rainout shelters, and in a second field environment with natural drought. Under water stress in mesocosms, lines with the FL phenotype had substantially less lateral root respiration per unit of axial root length, deeper rooting, greater leaf relative water content, greater stomatal conductance, and 50% greater shoot biomass than lines with the MS phenotype. Under water stress in the two field sites, lines with the FL phenotype had deeper rooting, much lighter stem water isotopic signature, signifying deeper water capture, 51% to 67% greater shoot biomass at flowering, and 144% greater yield than lines with the MS phenotype. These results entirely support the hypothesis that reduced lateral root branching density improves drought tolerance. The FL lateral root phenotype merits consideration as a selection target to improve the drought tolerance of maize and possibly other cereal crops.